Patient Centeredness from a Perspective of History of the Present: A Genealogical Analysis - Eleni Siouta; Ulf Olsson (SAGE Publishing, 2020)
The overall aim of this study, performed in Sweden, was to problematize the contemporary national and transnational discourse on patient centeredness, which during recent decades has become a given, having become established as a dogma in conversations, writing, and thinking about patients and health care. We did that by showing that ideas such as patient centeredness can be seen differently from the way they are depicted in contemporary discourses about health care. In the presented analysis, we drew on Foucault's concepts of governmentality, 'history of the present' and genealogy. This means that we reflected on contemporary conceptions of how phenomena, such as the care seeker, have been constructed within other discourses about health care. Empirically, we used different health policy documents-government reports from three different historical periods. The analysis showed that contemporary narratives about centeredness are neither more, nor less, care seeker-centered than the narratives of yesteryear. Rather, the phenomenon of the care seeker is given different frames and meanings within the framework of different economic and historical discourses about health care. Our analysis raised questions about the contemporary construction of patient centeredness. In a world with such huge economic differences between nations, as well as between citizens within most nations, the contemporary discourse may be limited as it does not problematize structural issues in the same way as previous discourses had done. Perhaps what is needed today are national and international patient-centered or person-centered discourses which also discuss policies and practices that are population- and social group-centered. In the final discussion of the analysis, we identified a new patient-centered discourse, which views the patient as a resource among other resources. The most important limitation of this type of study is that it is only about discourses and policy issues and not about daily practical activities.